Optimization of cutting parameter under mql nanolubricant approach during cnc turnin using taguchi method - Mohd Faizul Izwan Ibrahim (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Turning is one of the most important pocesses used in vareuous industrial application. usually the quality of finished part in turning operation is measured in terms of surface finish. In turn, surface quality and tool wear is determined by machining parameters that is cutting speed, feed rate, and depth of cut. The objective of this study is to investigate the effect of cutting parameters on surface finish and toolwear under MQL nanolubricant during turning operation of inconel 718.